Force-angle characteristics and level of competitive representation in on-water rowing - Warmenhoven, J.; Cobley, S.; Draper, C.; Harrison, A.; Bargag, N.; Smith, R. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The graphical presentation of the propulsive form applied by the oar to the pin, plotted against the oar horizontal angle, has been used as a diagnostic tool for rowing skill. How the pattern is related to variables such as level of competitive has not been well identified. Bivariate functional principal components analysis (bfPCA) was used on form-angle data to identify the main modes of variation in curves representing twenty seven female rowers of two different competition levels (Australian Domestic and Australian International level), rowing at 32 strokes per minute in a single scull boat. Discriminant function analysis showed strong classification of rowers using force-angle graphs across both sides of the boat, with increased rate of force development identified as an important characteristic for international rowers. Additionally for the bow-side, spending less time in the first half of the drive phase was also identified as an important feature for international rowers. The results of this demonstrate that there are potentially some common characteristics of the form-angle that are important for selection in international level sculling boats.